The Philosophy of J.J. Abrams - Arp, Robert; Brace, Patricia, 1960- (Book collections on Project MUSE., 2014)
American auteur Jeffrey Jacob ""J. J."" Abrams's genius for creating densely plotted scripts has won him broad commercial and critical success in TV shows such as Felicity (1998--2002), Emmy-nominated Alias (2001--2006), Emmy and Golden Globe-winning Lost (2004--2010), and the critically acclaimed Fringe (2008--2013). In addition, his direction in films such as Cloverfield (2008), Super 8 (2011), and the new Mission Impossible and Star Trek films has left fans eagerly awaiting his revival of the Star Wars franchise. As a writer, director, producer, and composer, Abrams seamlessly combines geek.